Analytical Estimation of Induced Voltage in Rotating Electrical Machines - Marius Meiswinkel; Amir Ebrahimi; Anjali Biju (IEEE Access)
Whether for the estimation of circulating current in the parallel circuits of the stator winding, damper current in the rotor of a synchronous machine, or voltage oscillation in the stator winding, an exact calculation of induced voltage is always inevitable. However, even when using FEM software, this voltage estimation is a post-process calculation based on pre-calculated flux densities or vector potentials. Since the air gap flux density is the primer parameter used in analytical estimations, it is therefore desirable to have a general and programmable method for calculating induced voltages regardless of their origin based on the air gap flux density. The rotating Tensor and its projection function offer a suitable alternative for these kinds of estimations. In this paper, the projection function is used to present a general method of estimating induced voltage in rotating machines with different winding topologies. This has been done for integer and fractional multi-layer windings in different machines, as well as the damper bars in the rotor. The results are compared to FEM calculation.